Penggunaan Mobile Apps Kesehatan oleh Kader Pada Anjungan Mandiri Posyandu (AMP) Di Kecamatan Pasawahan, Purwakarta - Ari Indra Susanti; Fedri Ruluwedrata Rinawan; Indah Amelia (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Background: Government needs community empowerment especially in Posyandu activity to improve health degree in Indonesia. Posyandu is the spearhead in maternal and child health services. Therefore, the cadre is a driver in Posyandu activities so that innovation is needed for an application to assist the task of cadres in reporting and recording of maternal and child health data.Objective: This study aims to determine the linkage of government policy in the use of mobile application apps by cadres on Anjungan Mandiri Posyandu (AMP).Method: The research method used is qualitative with case study approach. This research was conducted on active cadre in Posyandu of Pasawahan Village Kidul Subdistrict of Pasawahan Purwakarta Regency on May to July 2017. The data was collected by Focus Group Discussion (FGD) on 15 cadres. Sampling technique using purposive sampling. Results: The results of this study found that the recording and reporting of data in the form of Posyandu Information System (SIP) by cadres using AMP.Conclusion: It can be concluded in this research that with the application of mobile apps health on AMP can assist duty cadre in recording and reporting data to health center. Therefore, government policies are needed in the use of AMP for Posyandu in Indonesia.Keywords: Anjungan Mandiri Posyandu, Policy, Mobile Apps